Standardization of measurements of 25-Hydroxyvitamin D3 and D2 - Thienpont, Linda M.; Stepman, Hedwig C. M.; Vesper, Hubert W. (Scandinavian journal of clinical & laboratory investigation. Supplement, 2012)
Abstract The vitamin D status is increasingly assessed/monitored in different populations, research cohorts and individual patients. This is done by measuring the liver metabolites 25-hydroxyvitamin D3 and D2 as biomarkers. Recommendations for using specific serum concentrations of these biomarkers to assess a person's vitamin D status were done. This requires current vitamin D assays to be sufficiently accurate over time, location and laboratory procedures. In view of the fact that several studies demonstrated that current 25(OH)D measurement methods do not meet this prerequisite, standardization is needed. This paper rehearses the basic concept of standardization, in particular applied to measurements of 25-hydroxyvitamin D. Progress has been made by establishing a reference measurement system consisting of reference methods and reference materials. Coordinated efforts to improve the accuracy and standardize measurements are being performed by organizations such as the U.S. NIH, the CDC and Prevention, the NIST together with their national and international partners. Beyond describing the available reference measurement system and its use as calibration hierarchy to establish traceability of measurements with routine laboratory methods to the SI-unit, this report will also focus on other aspects considered essential for a successful and sustainable standardization, such as analytical issues related to the definition of the measurand and analytical performance goals.